Inactivation of polygalacturonase and pectate lyase produced by pH tolerant fungus Fusarium moniliforme NCIM 1276 in a liquid medium and in the host tissue - Niture, Suryakant K.; Kumar, Ameeta R.; Parab, Pradeep B.; Pant, Aditi (Microbiological Research, 2008)
Fusarium moniliforme NCIM 1276 produced pH dependent an extracellular potygalacturonase (PG) and pectate lyase (PL) at pH 5 and pH 8, respectively. In the extracellular medium about 20.3% PG and 54% of PL protein concentrations were present in the active state at pH 5 and pH 8, respectively, whereas in intracelluarly, more than 86% of both protein contents remained in the active state at all pH tested. We found two possible reasons, end-product inhibition and effect of environmental. pH on conformation of the proteins after their release into the medium. Additionally, in infected tomato and cauliflower plants, the fungus secreted similar proteins which were located near to the epidermal and vascular regions of the hypocotyts. In infected tissues, between 26.9% and to 41.5% of PG and only 0.84% - 13.4% of PL protein concentrations were present in active state. Thus, the medium/cell sap pH and concentrations of substrate/end products seem to play an important role in fungal invasion during plant pathogenesis are discussed with current literature. (c) 2006 Elsevier GmbH. All rights reserved.
Keywords: Fusarium moniliforme; pathogenesis; pectate lyase; polygatacturonase

Penicillin V acylases from gram-negative bacteria degrade N-acylhomoserine lactones and attenuate virulence in Pseudomonas aeruginosa - Sunder, Avinash Vellore; Utari, Putri Dwi; Ramasamy, Sureshkumar; van Merkerk, Ronald; Quax, Wim; Pundle, Archana (Applied Microbiology and Biotechnology, 2017)
Virulence pathways in gram-negative pathogenic bacteria are regulated by quorum sensing mechanisms, through the production and sensing of N-acylhomoserine lactone (AHL) signal molecules. Enzymatic degradation of AHLs leading to attenuation of virulence (quorum quenching) could pave the way for the development of new antibacterials. Penicillin V acylases (PVAs) belong to the Ntn hydrolase superfamily, together with AHL acylases. PVAs are exploited widely in the pharmaceutical industry, but their role in the natural physiology of their native microbes is not clearly understood. This report details the characterization of AHL degradation activity by homotetrameric PVAs from two gram-negative plant pathogenic bacteria, Pectobacterium atrosepticum (PaPVA) and Agrobacterium tumefaciens (AtPVA). Both the PVAs exhibited substrate specificity for degrading long-chain AHLs. Exogenous addition of these enzymes into Pseudomonas aeruginosa greatly diminished the production of elastase and pyocyanin and biofilm formation and increased the survival rate in an insect model of acute infection. Subtle structural differences in the PVA active site that regulate specificity for acyl chain length have been characterized, which could reflect the evolution of AHL-degrading acylases in relation to the environment of the bacteria that produce them and also provide strategies for enzyme engineering. The potential for using these enzymes as therapeutic agents in clinical applications and a few ideas about their possible significance in microbial physiology have also been discussed.
Keywords: N-acylhomoserine lactone acylase; Ntn hydrolase; pathogenesis; Penicillin Vacylase; Quorum quenching

Insights of Bipolaris sorokinianasecretome-anin silicoapproach - Pathak, Gauri M.; Gurjar, Gayatri S.; Kadoo, Narendra Y. (Biologia, 2020)
The plant pathogen,Bipolaris sorokiniana(teleomorph:Cochliobolus sativus), is of global concern as it attacks many economically important cereals and grasses. During the infection process, phytopathogenic fungi are known to secrete a variety of proteins collectively known as the secretome, analyzing which can help in deciphering the mechanism of fungal pathogenesis. In this study, we performedin silicosecretome analysis ofC. sativusstrain ND90Pr using established secretome prediction pipeline involving software tools such as SignalP, TargetP, TMHMM, big-PI Fungal Predictor, ProtComp, and WoLF PSORT. Using these software and other prediction criteria, we identified 196 probable secretory proteins from theB. sorokinianaproteome. Characterization of the predicted secretome revealed proteins that may have probable functions in degradation of the plant cell wall, lipids, proteins, and nucleic acids, as well as in pathogenesis and metabolism. Further, the PHI-base analysis identified 38 proteins having a possible role in pathogenicity and virulence. This study helped to predict the composition of the secretome ofB. sorokinianaand extrapolate its role in plant infection and pathogen survival. It may provide clues for developing new control strategies targeting the vital fungal secretory proteins.
Keywords: Cochliobolus sativus; pathogenesis; Phytopathogenic fungi; Secretory proteins; Virulence

Systemic review on fitness and survival of salmonella in dynamic environment and conceivable ways of its mitigation - Sutar, Ajit A.; Dashpute, Rohit S.; Shinde, Yashodhara D.; Mukherjee, Srestha; Chowdhury, Chiranjit (Indian Journal of Microbiology, 2024)
Gastroenteritis caused by non-typhoidal Salmonella still prevails resulting in several recent outbreaks affecting many people worldwide. The presence of invasive non-typhoidal Salmonella is exemplified by several characteristic symptoms and their severity relies on prominent risk factors. The persistence of this pathogen can be attributed to its broad host range, complex pathogenicity and virulence and adeptness in survival under challenging conditions inside the host. Moreover, a peculiar aid of the ever-changing climatic conditions grants this organism with remarkable potential to survive within the environment. Abusive use of antibiotics for the treatment of gastroenteritis has led to the emergence of multiple drug resistance, making the infections difficult to treat. This review emphasizes the importance of early detection of Salmonella, along with strategies for accomplishing it, as well as exploring alternative treatment approaches. The exceptional characteristics exhibited by Salmonella, like strategies of infection, persistence, and survival parallelly with multiple drug resistance, make this pathogen a prominent concern to human health.
Keywords: Antibiotic resistance; Gastroenteritis; Non-typhoidal Salmonella; pathogenesis; Plant-derived metabolites; Salmonella pathogenicity islands; Type III secretion system